Association of lactation with maternal risk of type 2 diabetes: a systematic review and meta-analysis of observational studies. (November 2021) - Pinho-Gomes, Ana-Catarina; Morelli, Georgia; Jones, Alexandra; Woodward, Mark
Abstract: Background: Evidence of the effects of lactation on maternal risk of type 2 diabetes is conflicting, with some studies suggesting a protective effect, whereas others report no association. This study aimed to investigate the association between lactation and maternal risk of type 2 diabetes. Methods: We did a systematic review and random-effects meta-analysis of observational studies investigating the association between lactation (irrespective of duration, intensity, or mode) and maternal risk of type 2 diabetes. Bibliographic databases MEDLINE and Embase were searched from inception to Feb 28, 2021, with MeSH terms for lactation, breastfeeding, and type 2 diabetes. No restrictions were applied to type of study or language. This search was complemented with hand-searching of reference lists of relevant studies. The methodological quality of eligible studies was assessed using the Newcastle-Ottawa Scale for non-randomised studies. Heterogeneity was quantified using the I 2 statistic and tested using Cochran's Q test. Eligible studies were included in the meta-analysis if they had published data on the outcomes of interest in each analysis. This study is registered with PROSPERO, number CRD42020221183. Findings: Our search identified 1161 studies, of which 22 (17 cohort and five cross-sectional) were eligible for inclusion in the systematic review (8739 participants), and 16 contributed to the meta-analysis (4372 participants). The studies were conducted in populations from North America, Europe, Asia, and Australia, including multi-ethnic populations and variable sample sizes (range 100–83 000). The five studies that investigated the association of lactation with risk of type 2 diabetes in the first months after birth in women with gestational diabetes reported conflicting results. The 17 studies with longer follow-up (>3 months) showed an incremental (dose–response) protective association between lactation and risk of type 2 diabetes, with a potentially larger risk reduction in women with gestational diabetes than in those without gestational diabetes (risk ratio [RR] 0·66 [95% CI 0·52–0·85] for ever vs never lactation for women with gestational diabetes, and RR 0·81 [0·67–0·98] for ever vs never lactation for women without gestational diabetes; p=0·032 for heterogeneity). Overall, ever versus never lactation was associated with a lower risk of type 2 diabetes (RR 0·73, 95% CI 0·65–0·83; I 2 =69%, p=0·010). Each additional month of lactation was associated with a 1% lower risk of type 2 diabetes (RR 0·99, 0·98–0·99), irrespective of gestational diabetes. The overall quality of the studies was modest. Interpretation: Lactation is associated with a significantly lower risk of maternal type 2 diabetes, particularly in women with gestational diabetes. The protective effect seems to increase with longer duration of lactation. Further research is warranted to understand whether this association is modified by exposure to other risk factors, such as obesity. Breastfeeding-friendly policies might help to reduce the risk of type 2 diabetes among women. Funding: None.